Legal Policy on Artificial Intelligent (AI): Study Comparative from Global Practices - Eka Nanda Ravizki; Lintang Yudhantaka; Rr. Chantika Vebyola Wijaya (Future Science, 2022)
AI development and its ever-growing practical use require changes in legal regulation, such as the need to restructure the legal system. Due to the absence of guidance concerning AI’s behavior from legislation, lawmakers must review the existing legal framework and adapt it to the changing needs of society. As an example, In Europe, in 2012, the European Commission initiated a RoboLaw Project with the main objective of investigating how emerging technologies in the field of bio-robotics (including AI) bear on the national and European legal systems. Then how about Indonesia? the discussions about AI and its influence on the law in Indonesia have not developed yet. It is also clear that Indonesia does not have any legal rules that discuss the existence of these smart robots. Therefore, there is an urgency to respond to the development of new technology in the world (especially in Indonesia) and to know the progress that has been made by other countries in welcoming the era of artificial intelligence. The result revealed that the governments in all-round the world faced similar challenges in conceptualizing criminal liability for AI crimes. They decided to focus on making legal policy regarding AI which can monitor the safety and fairness of AI, and adapt regulatory frameworks to encourage innovation while protecting the public